On the Relations Between Parents' Ideals and Children's Autonomy. Issue 4 (20th August 2013) - de Ruyter, Doret J.; Schinkel, Anders
Abstract In this article Doret J. de Ruyter and Anders Schinkel argue that parents' ideals can enhance children's autonomy, but that they may also have a detrimental effect on the development of children's autonomy. After describing the concept of ideals and elucidating a systems theoretical conception of autonomy, de Ruyter and Schinkel explore the ways in which the ideals of parents may play a role in the development of their children's autonomy. They show that abstract and complex ideals of parents (be it ideals for their children, ideals with regard to their parenthood, or their personal ideals) are most likely to enhance their children's autonomy. They also explain that an authoritative parenting style is most conducive to autonomy, although whether or not it does benefit children's autonomy also depends on the types of ideals pursued by parents.